Daniil Medvedev’s serve and return stability average percents at tournaments in the period of 2019-2023 - Al Khalili M.; Al Khalili S.M.; Chekalova E.V. (Theory and Practice of Physical Culture, 2023)
The relevance of the work lies in the study of some most important factors and aspects of the training and competition effectiveness, success and perfomance of any tennis player. In our article, we consider the dynamics of the changes in Daniil Medvedev’s serve and return stability average indicators at the Grand Slam tournaments in the period of 2019-2023. Processing and analyzing the video materials of 81 matches, we obtained results that determined the dynamics of changes in serve and return stability average indicators for up to 5 years. To assess the dynamics of changes more objectively in Daniil Medvedev’s serve and return stability indicators, we carried out a comparative analysis of the first serve and return winning points indicators.